Mengenal Fungsi Kognitif Dan Keseimbangan Postural Tubuh Pada Anak Down Syndrome - Dwi Rosella Komalasari; Tsania Haifa’ Kurniahadi; Fahra Fadhilla (jurnal ABDIMAS Indonesia, 2025)
Postural balance is a crucial aspect of daily life that enables individuals to move with stability and safety. Children with Down Syndrome (DS) often experience balance disorders due to cognitive function limitations that affect their motor abilities. This study aims to explore the relationship between cognitive function and balance in children with DS. Cognitive impairments, including memory deficits, attention difficulties, and executive function challenges, can impact a child's ability to control posture and perform motor activities effectively. Additionally, difficulties in movement coordination and sensorimotor responses contribute to poor balance abilities. Understanding the connection between cognitive function and balance can facilitate the implementation of appropriate interventions, such as physical therapy and cognitive stimulation, to improve the quality of life of children with DS. A holistic approach is essential in supporting the development of children with DS to help them achieve greater independence. Parents and families play a vital role in actively participating in the growth and development of children with DS, ensuring that their cognitive function and balance are maintained and enhanced. Consequently, children with DS can become more independent and socially engaged, enabling them to interact with others and build healthy social relationships. Keywords: Down Syndrome, cognitive function, postural balance, parents, family